IMPLEMENTASI PLATFORM SISTEM INFORMASI DESA (SIDESA) DALAM PENGUATAN SISTEM PELAYANAN ADMINISTRASI DAN KEPENDUDUKAN DIGITAL - Trisudarmo, Ragel; Mirantika, Nita; Syamfithriani, Tri Septiar; Riddwan, Iwan Mohammad; Ariani, Fitrah Ramadanti (LPPM Universitas Nusa Mandiri, 2025)
The digital-based transformation of the administrative and population service system has provided great positive benefits for society. The main problem faced by the community in Mancagar Village is dependence on manual processes in administrative management, which requires residents to come directly to the village office, thus creating a big challenge, especially for those who live outside the city. The aim of this program is to make it easier to access administrative and population services, optimize data archiving, and prepare open information for the public. The Technical Assistance method used in community service activities through this approach emphasizes the rapid changes to be achieved through several stages that have been prepared through training and assistance in managing the SIDESA website. This program implements SIDESA to provide administration services for letter issuance and population management that are more efficient, transparent and easily accessible. The results of this initiative demonstrate improved quality of public services, reduced barriers to access, and effective information technology education for the public. The evaluation shows that more than 50% of residents have understood this new system, thereby ultimately providing better and more efficient public services in Mancagar Village.